2009
DOI: 10.1007/s12263-009-0152-3
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive potential of curcumin in prostate cancer

Abstract: The long latency and high incidence of prostate carcinogenesis provides the opportunity to intervene with chemoprevention in order to prevent or eradicate prostate malignancies. We present here an overview of the chemopreventive potential of curcumin (diferuloylmethane), a well-known natural compound that exhibits therapeutic promise for prostate cancer. In fact, it interferes with prostate cancer proliferation and metastasis development through the down-regulation of androgen receptor and epidermal growth fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
96
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 110 publications
0
96
0
2
Order By: Relevance
“…Curcumin suppressed cell proliferation or induced apoptosis in cultured prostate cancer cells and other types of cancer cells (4)(5)(6)(7)(8)(9)(10). Curcumin also inhibited prostate carcinogenesis (11). Studies from our laboratory and those of other authors have demonstrated enhanced anticancer activities of curcumin when combined with other anticancer agents (12)(13)(14).…”
Section: Introductionmentioning
confidence: 64%
“…Curcumin suppressed cell proliferation or induced apoptosis in cultured prostate cancer cells and other types of cancer cells (4)(5)(6)(7)(8)(9)(10). Curcumin also inhibited prostate carcinogenesis (11). Studies from our laboratory and those of other authors have demonstrated enhanced anticancer activities of curcumin when combined with other anticancer agents (12)(13)(14).…”
Section: Introductionmentioning
confidence: 64%
“…Curcumin (diferuloylmethane), from the roots of Curcuma longa and well characterized for its anti-carcinogenic, anti-proliferative, anti-inflammatory, anti-angiogenic and anti-oxidant properties (12,13) was also shown to affect the Wnt signaling especially in colon, gastric, intestinal and breast cancer cells (14)(15)(16)(17). Studies evaluating the effect of curcumin on prostate cancer cell proliferation mainly focused on the impact of this natural compound on epidermal growth factor receptor (EGFR), on cyclins implicated in cell cycle and on phosphatidyl inositol 3-kinase (PI3)/Akt/mammalian target of rapamycin (mTOR) (18). Here we evaluate the effect of curcumin on prostate cancer cell proliferation by focusing on cell cycle and Wnt/ß-catenin in both androgen-dependent and independent prostate cancer cells, representative respectively of the early localized and late metastatic stages of prostate cancer development (19).…”
Section: Cyclooxygenase-2 (Cox-2) Matrix Metalloproteinase (Mmp) mentioning
confidence: 99%
“…Numerous studies have demonstrated the anticancer activity of curcumin and curcumin analogues in animal models [2][3][4][5][6][7] as well as growth inhibition and apoptosis induction in a variety of cancer cell lines in vitro. [8][9][10][11][12][13][14][15][16] However, the clinical efficacy of curcumin is limited, which is likely due to its low bioavailability. [17][18][19] We have previously reported on the synthesis and evaluation of sixty-one curcumin-related compounds for inhibitory effects on cultured prostate cancer cells, pancreatic cancer cells and colon cancer cells.…”
mentioning
confidence: 99%